Bibliometric Analysis of Agricultural Entrepreneurship - Loso Judijanto (Westscience Press, 2026)
This study aims to systematically map the intellectual structure, thematic evolution, and collaborative patterns of research on agricultural entrepreneurship through a bibliometric approach. Bibliographic data were collected from the Scopus and Web of Science databases, covering peer-reviewed articles published over multiple decades. Using VOSviewer, the study applied performance analysis and science mapping techniques, including keyword co-occurrence, co-authorship, institutional collaboration, and country network analyses. The results reveal that entrepreneurship constitutes the central conceptual foundation of the field, strongly interconnected with themes such as sustainability, innovation, agribusiness, and rural development. Temporal analysis indicates a clear shift from early research emphasizing institutional support, productivity, and government intervention toward more recent studies focusing on sustainability-oriented and technology-driven entrepreneurial models, including digital agriculture and agricultural robotics. Collaboration analysis shows a globally interconnected yet uneven research landscape, with scholarly output concentrated among a limited number of authors, institutions, and countries, particularly the United States, China, and India. This study contributes to the literature by providing a comprehensive overview of the evolution and current state of agricultural entrepreneurship research, offering valuable insights for scholars, policymakers, and practitioners, and identifying opportunities for future research and international collaboration in advancing sustainable and inclusive agricultural development⁠.